Decolonising education : An exploration in Bolivian-German relations - Kölbl, Carlos (cultura & psyché, 2022)
In this article I aim to contribute to a more multifaceted picture of what decolonising education can mean. I do this in the form of a case study of selected and intertwined Bolivian–German discourses and practices directed at the decolonisation of education in the wide sense of the term. First, I introduce Indigenist and ‘Indianist’ proposals, which are shaped, not least, by Nietzschean ideas. In a second step, I turn to some examples of German ‘Bildungsromane’ that are deeply entangled with Bolivian phenomena. Hence, the first part of the article is about decolonising the formerly colonised via education, whereas the second revolves around decolonising the former colonisers, but without the possibility for or the wish to identify completely clear-cut boundaries. It will thus become clearer how decolonising education can be understood as a relational phenomenon.
Keywords: Relationality; Indigenism; 'Indianism'; 'New Left' (West Germany); Trikont-Publishers